2005
DOI: 10.1021/ja050441o
|View full text |Cite
|
Sign up to set email alerts
|

η:η-Alkynyl-Bridged W−Si Complexes:  Formation, Structure, and Reaction with Acetone

Abstract: Reactions of (eta5-C5Me4R)(CO)2(MeCN)WMe (R = Me, Et) with HPh2SiCCtBu gave the novel alkynyl-bridged W-Si complexes, (eta5-C5Me4R)(CO)2W(mu-eta1:eta2-CCtBu)(SiPh2) (R = Me, Et), whose alkynyl ligands bridge the tungsten and silicon atoms in an eta1:eta2-coordination mode. The structures of these complexes were fully characterized, including X-ray crystallography. Treatment of (eta5-C5Me5)(CO)2W(mu-eta1:eta2-CCtBu)(SiPh2) with acetone resulted in acetone insertion into the silicon-alkynyl linkage followed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…The molecular structure of 4 indicates that the silylene ligand interacts with both the metal and the acetylide fragments, similar to 2b , but significant differences are found in their W−Si and Si−C2 bond distances. The W1−Si1 distance (2.5474(16) Å) of 4 is considerably shorter than that (2.567(2) Å) of 2b , whereas the Si1−C2 distance (2.059(6) Å) of 4 is significantly longer than that (2.008(7) Å) of 2b . These differences indicate stronger silylene−metal and weaker silylene−acetylide interactions in 4 than in 2b .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The molecular structure of 4 indicates that the silylene ligand interacts with both the metal and the acetylide fragments, similar to 2b , but significant differences are found in their W−Si and Si−C2 bond distances. The W1−Si1 distance (2.5474(16) Å) of 4 is considerably shorter than that (2.567(2) Å) of 2b , whereas the Si1−C2 distance (2.059(6) Å) of 4 is significantly longer than that (2.008(7) Å) of 2b . These differences indicate stronger silylene−metal and weaker silylene−acetylide interactions in 4 than in 2b .…”
Section: Resultsmentioning
confidence: 88%
“…Transition-metal silylene complexes have attracted much attention as possible intermediates in various metal-mediated reactions of organosilicon compounds, and recent studies have revealed the interesting reactivity of isolated silylene complexes . Recently, we reported the synthesis of the novel acetylide−silylene complexes Cp′(CO) 2 W(SiPh 2 )(CC t Bu) ( 2a , Cp′ = η 5 -C 5 Me 5 ; 2b , Cp′ = η 5 -C 5 Me 4 Et), which have unique structural features and bonding interactions (Scheme ) . In addition to the silylene−metal interaction, Sakaki’s theoretical study revealed dual charge transfer interactions between the acetylide and silylene ligands: from the π orbital of the acetylide to the empty p orbital of the silylene and from the lone pair orbital of the silylene to the π* orbital of the acetylide .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available t Bu–C≡CH and i Pr 2 Si(H)Cl were dried with molecular sieves; i PrMgCl in THF, n BuLi in n ‐hexane, CS 2 , CO 2 , i Bu 2 Al–H and Et 2 Al–H were used without further purification. t Bu 2 Al–H, [ 39 ] t Bu 2 Ga–H, [ 39 ] [(Me 3 Si) 2 CH] 2 Al‐H, [ 39 ] Me 2 Al–H [ 40 ] and Ph 2 Si(H)–C≡C‐ t Bu [ 41 ] were synthesized according to literature procedures. An optimized procedure for the synthesis of i Pr 2 GeCl 2 is given below.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts of purification by column chromatography failed; substituent exchange was initiated with the formation of diisopropyl-dialkynylgermane. 1 2 (1c): [41] Compound 1c was synthesized according to the procedure described for 1a from tBu-C≡CH (1.13 mL, 0.75 g, 9.15 mmol), nBuLi (5.7 mL, 9.14 mmol, 1.6 M in nhexane) and Ph 2 Si(H)Cl (1.79 mL, 2.00 g, 9.16 mmol) in Et 2 O (40 mL). After addition of the lithium alkynide to the silane solution the mixture was warmed to room temperature and heated under reflux overnight.…”
Section: Synthesis Of Tbu-c≡c-si(h)ipr 2 (1a): Nbulimentioning
confidence: 99%